Resistance characteristics of innovative eco-fitness equipment: a water buoyancy muscular machine - Chen, W.-H.; Liu, Y.-C.; Tai, H.-H.; Liu, C. (Sports Biomechanics, 2018)
This paper propose innovative eco-fitness equipment—a water buoyancy muscular machine (WBM machine) in which resistance is generated by buoyancy and fluid resistance. The resistance characteristics during resistance adjustment and under isometric, concentric, eccentric and isokinetic conditions were investigated and compared to a conventional machine with metal weight plates. The results indicated that the isometric, concentric and eccentric resistances could be adjusted by varying the water volume; the maximum resistances under isometric, concentric and eccentric conditions were 163.8, 338.5 and 140.9 N, respectively. The isometric resistances at different positions remained constant in both machines; however the isometric resistance was lower for WBM machine when at a position corresponding to a 5% total displacement. The WBM machine has lower resistance under eccentric conditions and higher resistance under concentric conditions. Although the conventional machine has an identical trend, the variation was minor (within 4 N). In the WBM machine, the eccentric resistance was approximately 30-45% of the concentric resistance. Concentric resistances increased with an increase in velocity in both machines; however, the eccentric resistances decreased with an increase in velocity. In summary, the WBM machine, a piece of innovative eco-fitness equipment, has unique resistance characteristics and expansibility.